Factors Affecting the High School Users’ Information Needs in the Public Libraries of Mashhad City - Asefeh Asemi; Bibi Eshrat Zamani; Amin Mirzaei (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2012)
Purpose: The purpose of the present research is to study the factors that affect the high school users’ information needs in the public libraries of Mashhad city affiliated to the general office of public libraries foundation based on individual, social, educational, and religious factors. Method: The research method is a survey method, and the statistical population includes all high school users in the mentioned libraries. Based on Kerjcie and Morgan’s sample size table, 346 users were selected as the research sample. The data were collected by giving a researcher-made questionnaire whose validity and reliability were calculated by factor analysis and Cronbach’s Alpha co-efficient. The collected data were analyzed by descriptive (frequency, percentage, mean, median, and standard deviation) and inferential (single variable, T-test, and MANOVA multi variables variance analysis) statistics. Findings: The findings showed that individual and educational factors have the most influence on public libraries users’ information needs and social while economic factors have less influence than the two previous factors, and religious factor has the least influence with the average of 3.98%. Originality/Value: In case the students’ information needs are identified, it can be useful to provide them with the necessary resources and increase their interest in library environments. In order to achieve these goals, this study was to determine the role of each effective individual, social, economic, and religious factors in youth and students’ information needs. The results of this study can be used for planning libraries and other learning centers